Measuring communication styles in the Malaysian workplace: Instrument development and validation - Abu Bakar, Hassan; Walters, Timothy; Halim, Haslina (Routledge, 2014)
The aim of the present study is to access communication style in the Malaysian work- place through the development and validation of a communication scale appropriate to the Malaysian workplace.The analysis involved data from 200 state development employees, and construct and criterion-related validation using data from 510 employees, representing three organizations in Malaysia.The results provided support for the use of language (pekerti) and communication and interaction (bicara) as crucial communication dimensions for the Malaysian workplace, which are identified from the item-generation procedure.